On a family of quotients of the von Dyck groups - Dennis, Mark (2017)
In this publication, we investigate the groups H(m, n, p, q |k) defined by the presentation <x, y|x^m, y^n, (xy)^p, (xy^k)^q> and determine finiteness and infiniteness for these parameters as far as possible using geometric arguments, principally through pictures and curvature. We state and subsequently prove theorems relating to infiniteness, and also discuss troublesome cases where spherical pictures may arise. We also provide a list of known finite groups and unresolved cases in Appendix A.